2019
DOI: 10.1080/21691401.2019.1594860
|View full text |Cite
|
Sign up to set email alerts
|

Gold nano particles synthesized from Strychni semen and its anticancer activity in cholangiocarcinoma cell (KMCH-1)

Abstract: View related articles View Crossmark data Citing articles: 2 View citing articles Gold nano particles synthesized from Strychni semen and its anticancer activity in cholangiocarcinoma cell (KMCH-1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Possible molecular mechanisms of these herbs and/or isolated compounds/synthetic analogs on CCA cells involve induction of apoptosis, autophagy, and cell cycle arrest (at G 0 /G 1 , G 1 , G 1 /S, or G 2 /M phases) through suppression of proinflammatory cytokines and growth factors (IL6, EGF, VEGF, etc.) 10 , 13 , 23 , 27 , 28 , 29 , 30 , 32 , 34 , 36 , 41 , 43 , 46 , 51 , 52 , 53 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , suppression of expression of cell surface receptors ( Vegfr2 , EGFR peroxisome proliferator-activated receptor gamma, DR4 and DR5, and TRAIL) 69 , 86 , 87 , 88 , and deregulation of intracellular pathways (JAK/STAT3, RAS/MAPK, PI3K/AKT, GSK β / β -catenin, NF κ B/AMPK, ERK, p38/MAPK, HO1, ROS/JNK, EGFR, VEGF, COX2, FAK, MMP2, MMP9, ICAM1, caspase-3, -8, and − 9, TR1, MDR1, MRP1, 2, and 3, TRAF1, XIAP, p21, p53, p65, and CHOP dependent) ( Fig. 2 ) 7 , 11 , 16 , 19 ,…”
Section: Resultsmentioning
confidence: 99%
“…Possible molecular mechanisms of these herbs and/or isolated compounds/synthetic analogs on CCA cells involve induction of apoptosis, autophagy, and cell cycle arrest (at G 0 /G 1 , G 1 , G 1 /S, or G 2 /M phases) through suppression of proinflammatory cytokines and growth factors (IL6, EGF, VEGF, etc.) 10 , 13 , 23 , 27 , 28 , 29 , 30 , 32 , 34 , 36 , 41 , 43 , 46 , 51 , 52 , 53 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , suppression of expression of cell surface receptors ( Vegfr2 , EGFR peroxisome proliferator-activated receptor gamma, DR4 and DR5, and TRAIL) 69 , 86 , 87 , 88 , and deregulation of intracellular pathways (JAK/STAT3, RAS/MAPK, PI3K/AKT, GSK β / β -catenin, NF κ B/AMPK, ERK, p38/MAPK, HO1, ROS/JNK, EGFR, VEGF, COX2, FAK, MMP2, MMP9, ICAM1, caspase-3, -8, and − 9, TR1, MDR1, MRP1, 2, and 3, TRAF1, XIAP, p21, p53, p65, and CHOP dependent) ( Fig. 2 ) 7 , 11 , 16 , 19 ,…”
Section: Resultsmentioning
confidence: 99%
“…Caspases are a family of protease enzymes, which play major roles in the events of apoptosis. Specifically, the initiators caspase-8 and caspase-9 trigger the executioner caspase-3 by cleavage activation, leading to the proteolysis of poly(ADP-ribose) polymerase (PARP) and apoptosis through impairment of DNA repair [13]. Here, we show that treatment of HepG2 cells with gold nanoparticles with C. militaris extract induced caspase-3 activation to enhance apoptosis.…”
Section: Introductionmentioning
confidence: 85%
“…The chemical components of SS are complex and diverse, that mainly including alkaloids, phenolic acids, terpenoids, steroids and glycosides 9 13 . Modern pharmacological studies showed that SS has significant pharmacological effects in anti-tumor 14 , anti-rheumatism 15 , analgesia 16 , neuroprotection 17 and other diseases. SS contains a variety of monomers and acts on a variety of cell targets.…”
Section: Introductionmentioning
confidence: 99%